THE INFLUENCE OF JIGSAW TECHNIQUE AND SPEAKING ANXIETY TOWARD STUDENT’S SPEAKING COMPETENCE - Desi Surlitasari Dewi; Aulia Putri (CAHAYA PENDIDIKAN, 2016)
Lately, innovative models to teach English have been widely discussed. Communicative competence is definitely the goal when we teach speaking to foreign language learners. However, the goal was rarely achieved in speaking class. In this study, one of technique in Cooperative Learning, jigsaw technique, was proposed. It was predicted that jigsaw technique of teaching speaking and student’s speaking anxiety had effect toward student’s speaking competence. Jigsaw is a technique that can be used in speaking class as it assigns the students to work in team, where they tend to feel secured and comfortable to learn speaking. While speaking anxiety could be a language barrier distracting the students to succeed in speaking class. It is an internal factor from the student’s mind which prevents them from delivering communicative competence. Thus, the objectives of the study were to find out the effectiveness of jigsaw technique in teaching speaking as well as the influence of speaking anxiety, one of psychological factors in learning foreign language, towards the student’s speaking competence. The population of the research was the first semester students of English Department Universitas Riau Kepulauan. The research method was a quasi experiment and the data were taken by using a speaking test and questionnaires. Students’ speaking competences were assessed based on six categories namely fluency, task, comprehension, grammar, pronunciation, and vocabulary. While Saito’s speaking anxiety questionnaire was used to reveal student’s speaking anxiety. Then, the data were analyzed by using Anova. Keywords: jigsaw technique, speaking anxiety, speaking competence